Relationship between female genital tract infections, mucosal interleukin‐17 production and local T helper type 17 cells. Issue 4 (23rd October 2015) - Masson, Lindi; Salkinder, Amy L.; Olivier, Abraham Jacobus; McKinnon, Lyle R.; Gamieldien, Hoyam; Mlisana, Koleka; Scriba, Thomas J.; Lewis, David A.; Little, Francesca; Jaspan, Heather B.; Ronacher, Katharina; Denny, Lynette; et al.
Summary: T helper type 17 (Th17) cells play an important role in immunity to fungal and bacterial pathogens, although their role in the female genital tract, where exposure to these pathogens is common, is not well understood. We investigated the relationship between female genital tract infections, cervicovaginal interleukin‐17 (IL‐17) concentrations and Th17 cell frequencies. Forty‐two cytokines were measured in cervicovaginal lavages from HIV‐uninfected and HIV‐infected women. Frequencies of Th17 cells (CD3 + CD4 + IL‐17a + ) were evaluated in cervical cytobrushes and blood by flow cytometry. Women were screened for Chlamydia trachomatis, Neisseria gonorrhoeae, Mycoplasma genitalium, Trichomonas vaginalis and herpes simplex virus 2 by PCR, and candidal infections and bacterial vaginosis by Gram stain. Women with bacterial sexually transmitted infections (STIs), specifically chlamydia and gonorrhoea, had higher genital IL‐17 concentrations than women with no STI, whereas women with candidal pseudohyphae/spores had lower IL‐17 concentrations compared with women without candidal infections. Viral STIs (herpes simplex virus 2 and HIV) were not associated with significant changes in genital IL‐17 concentrations. Genital IL‐17 concentrations correlated strongly with other inflammatory cytokines and growth factors. Although Th17 cells were depleted from blood during HIV infection, cervical Th17 cell frequencies were similar in HIV‐uninfected and HIV‐infected women. Cervical Th17 cell frequencies were also not associated with STIs or candida, although few women had a STI. These findings suggest that IL‐17 production in the female genital tract is induced in response to bacterial but not viral STIs. Decreased IL‐17 associated with candidal infections suggests that candida may actively suppress IL‐17 production or women with dampened IL‐17 responses may be more susceptible to candidal outgrowth